A Late Palaeolithic Flint Workshop at Egtved, East Jutland: A Glimpse of the Federmesser Culture in Denmark - Fischer, Anders (Journal of Danish Archaeology, 1988)
A Late Palaeolithic Flint Workshop at Egtved, East Jutland - A Glimpse of the Federmesser Culture in Denmark